ENHANCING THE COMPETITIVENESS OF MICRO, SMALL AND MEDIUM ENTERPRISES CLUSTERS IN LAMONGAN REGENCY THROUGH DIGITAL MARKETING WITH GOVERNMENT POLICY AS A MODERATING VARIABLE - Sani Rusminah; Syairozi , Muhamad Imam; Dzikri, Mas Wahyu Ali; Al Fiqri, Muhammad Murtadho; Faqeh , M Masbukin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Urgency study This done Because the importance of Micro, Small and Medium Enterprises (MSMEs) for the economy in Indonesia which is not only become backbone in move wheel economy will but MSMEs also play a role as creator field Work as well as sustainability economy . Goal study namely analyze the influence of digital marketing on Power MSMEs competitiveness in the Regency Lamongan, analyzing influence policy government to Power MSME competitiveness in the Regency Lamongan , analyzing policy government moderate connection between digital marketing and power MSMEs competitiveness in the Regency Lamongan . The method used in study namely method quantitative with do survey use distributed questionnaires​ to respondents. Research This apply purposive sampling technique for determine sample. Respondents in the study This namely perpetrator MSMEss Center businesses in the Regency Lamongan , totaling 190 respondents . Method research data analysis use Partial Least Square (PLS) derived from from the Structural Equation Modeling (SEM) model with approach Second order confirmatory factor analysis. Research results This namely mark coefficient track of 0.604, t-statistic 13.865, and p-value 0.000 indicates that the more optimal the implementation of digital marketing, the more the more power also increases Company competitiveness , value coefficient path 0.336, t-statistic 5.072, and p-value 0.000, meaning support policy government capable strengthen position Power competition whereas mark coefficient 0.285, t-statistic 2.707, and p-value 0.007, meaning policy government play a role as variables strengthening moderation​ the influence of digital marketing on Power competitive .